TRANSFORMATIVE LEADERSHIP AND JOB SATISFACTION IN THE NURSING PROFESSION: A NARRATIVE REVIEW - Carla Rizzo; Flavio Marti; Luca Perrozzi; Lucia Mauro (OPI Napoli, 2024)
Introduction: Healthcare organisations require optimal leadership to achieve goals and deliver high-quality services. Leadership is the ability to influence employee behaviour and beliefs and is an essential element of a successful organisation. Improving job satisfaction is a key objective in addressing the challenges related to achieving and maintaining quality standards, ensuring patient satisfaction and staff retention. Similarly, transformational leadership has positive effects on nurses' job satisfaction and promotes organisational wellbeing in the workplace. Objective: The purpose of the review is to describe transformational leadership and job satisfaction in the nursing profession through a narrative revision. Materials and methods: The bibliographic research was carried out between September 2022 and March 2024 by consulting databases such as PubMed, CINAHL, and PsycInfo, with time limits of 12 years and Italian and English language filters. All items deemed relevant have been stored and managed with the Zotero IT platform. Results: 16 studies were examined: 1 comparative study, 5 descriptive correlational studies, 1 meta-analysis, 1 systematic review, 4 cross-sectional studies, 2 mixed method studies and 2 unspecified studies. The results of this study are consistent with transformational leadership theory, which highlights the leader's role in providing employees with supportive work environments that result in higher levels of job satisfaction and efficiency. Conclusions: The skills of a transformative leader, such as the ability to listen, provide support, and promote fairness and recognition, are fundamental to increasing nurses' job satisfaction and sustaining environments with a high level of quality of care. Healthcare managers must protect the quality of work undertaken by staff, implementing strategies that can improve nurses' working conditions.